Experimental study on hydrodynamic performance of SWATH vessels in calm water and in head waves. (April 2019) - Begovic, E.; Bertorello, C.; Bove, A.; De Luca, F.
Highlights: Four SWATH hull forms have been tested in calm water and in regular waves. Dynamic instability peculiar for SWATH at higher relative speed is investigated. Active stabilisation was developed and fitted to SWATH #5 and tested in calm water, regular and irregular waves. Active stabilization made possible to reach higher speed and very low vertical motions. Comparison of different hull forms assures significant database for small craft SWATH design and research. Abstract: An extensive experimental investigation on four SWATH hull forms has been conducted in calm water and in regular waves at University of Naples Federico II. Calm water tests have been analyzed in the range of Froude number F rT from 0.1 to 0.6. For all four SWATH configurations at the speed, corresponding to F rT 0.32, the behaviour in regular waves has been tested. The results of heave, pitch and vertical accelerations are presented in nondimensional form as RAO. For the "most promising" SWATH #4 configuration, a set of stabilizing fins have been designed and an active stabilization system has been developed. The developed SWATH#5 has been tested in calm water on three displacements in the range of F rT from 0.1 to 0.65. The dynamic wetted surface has been identified and the residual resistance coefficient CR as well as R T /Δ are reported. Seakeeping tests have been performed in regular head sea and in head and following irregular sea at F rT = 0.50. The conditions for the occurrence of dynamic longitudinal instabilities have been identified. The results allows to comment the effect of slenderness of struts and SWATH's immersed bodies on resistance and seakeeping and concerns the applicability of SWATH concept to small craft.